Assessment of Policy Instruments Toward a Sustainable Traffic System -A backcasting approach for Stockhom 2030 - Markus Robèrt; Daniel Jonsson R. (European Regional Science Association (ERSA), 2005)
Finding strategies for preventing the process of global warming is growing urgent. Our intention is to highlight the future requirements and expectations on transport related sustainability measures (e.g. mobility management services, road tolls, CO2-taxes and renewable fuel systems) assisting the reaching of a long-term sustainability target of greenhouse gas emissions at the year 2030. We will employ the transport demand model SAMPERS and the traffic assignment model EMME/2 in order to investigate the effect from specific changes to the traffic network of Stockholm 2030, e.g. the environmental and socioeconomic impact from reduced number of commute trips, reduced car ownership, and new price structures and restrictions on private vehicle travel. In connection to this, we also quantify negative side effects (so-called rebound effects) coupled to efficiencies in the traffic network. We use an appraisal framework, influenced by backcasting, in order to assess the impact from the specific policies in relation to the United Nation's (IPCC) requirements for a sustainable level of CO2-emissions. The findings from this study point at the inevitable need for at least a 50% renewable fuel mix in the traffic system if reaching the target 2030. Single-handedly, travel demand measures are insufficient to accomplish the CO2-emission target for 2030. Nevertheless, reducing traffic volumes by just a few percent might contribute to savings in emission costs, accident costs and aggregate travel time costs in the traffic system. Such measures are needed in order to mitigate the transition from fossil- to renewable fuels.
Keywords: 330